1995
DOI: 10.1073/pnas.92.14.6469
|View full text |Cite
|
Sign up to set email alerts
|

Illusory contours activate specific regions in human visual cortex: evidence from functional magnetic resonance imaging.

Abstract: The neural basis for perceptual grouping operations in the human visual system, including the processes which generate illusory contours, is fundamental to understanding human vision. We have employed functional magnetic resonance imaging to investigate these processes noninvasively. Images were acquired on a GE Signa 1.5T scanner equipped for echo planar imaging with an in-plane resolution of 1.5 x 1.5 mm and slice thicknesses of 3.0 or 5.0 mm. Visual stimuli included nonaligned inducers (pacmen) that created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
116
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 36 publications
20
116
4
Order By: Relevance
“…Similarly, brain activity related to the perception of illusory contours using Kanizsa triangle elicited significant activation in early visual areas (Ffytche & Zeki, 1996;Hirsch et al, 1995) and imagining a visual detail with high resolution causes early visual cortex activation (Kosslyn & Thompson, 2003). During dreams subjects do not often report perceiving objects with a very high degree of detail, which is congruent with the relative quiescence of early visual cortices during REM sleep (e.g.…”
Section: Neuroimaging Of Illusion and Sensory Imagerymentioning
confidence: 74%
“…Similarly, brain activity related to the perception of illusory contours using Kanizsa triangle elicited significant activation in early visual areas (Ffytche & Zeki, 1996;Hirsch et al, 1995) and imagining a visual detail with high resolution causes early visual cortex activation (Kosslyn & Thompson, 2003). During dreams subjects do not often report perceiving objects with a very high degree of detail, which is congruent with the relative quiescence of early visual cortices during REM sleep (e.g.…”
Section: Neuroimaging Of Illusion and Sensory Imagerymentioning
confidence: 74%
“…However, the poor temporal resolution of these methods cannot differentiate feed-forward vs. feedback mechanisms contributing to the same effect. In a first blocked-design fMRI study of 4 healthy subjects, regions in extra-striate visual cortex -most likely area V2 -responded preferentially to IC presence [62]. These results were considered as "consistent with a data-driven, bottom-up approach to illusory-contour perception" (p. 6472 of [62]; see also [63] for nearly 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 contemporaneous PET results).…”
Section: Hemodynamic Imagingmentioning
confidence: 99%
“…In a first blocked-design fMRI study of 4 healthy subjects, regions in extra-striate visual cortex -most likely area V2 -responded preferentially to IC presence [62]. These results were considered as "consistent with a data-driven, bottom-up approach to illusory-contour perception" (p. 6472 of [62]; see also [63] for nearly 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 contemporaneous PET results). Another blocked-design fMRI study [64] and V1 when viewing ICs but not real contours (see also [17] for qualitatively similar findings in monkeys), which was taken as consistent with the role of feedback signals, potentially originating from the fusiform gyrus [65].…”
Section: Hemodynamic Imagingmentioning
confidence: 99%
“…absence of illusory Kanizsa square. The first goal was to investigate whether there was right hemispheric lateralisation in brain activation, as suggested by several studies [14]. Secondly the study aimed at understanding if illusory contour formation occurred at early stages of visual processing pathways or if it involved associative higher level cortical regions.…”
Section: 242mentioning
confidence: 99%
“…Besides the right-sided activation of the fusiform gyrus recorded in the Larsson et al [19] PET study, there seems to be further evidence of hemispheric asymmetry. For instance Hirsch et al [14] in the fMRI study showed the predominance of brain activity related to illusory contours perception in the right extra-striate area. According to Hirsch et al brain activation could involve striate cortex (area 17), too.…”
Section: Introductionmentioning
confidence: 99%